Consequences of an Extended Recruitment on Participation in the Follow‐Up of a Child Study: Results from the German IDEFICS Cohort. Issue 1 (21st November 2016) - Langeheine, Malte; Pohlabeln, Hermann; Ahrens, Wolfgang; Rach, Stefan
Abstract: Background: Declining response proportions in population‐based studies are often countered by extended recruitment efforts at baseline that may, however, result in higher attrition in a subsequent follow‐up. This study analysed the effect of extended recruitment efforts on attrition at the first follow‐up of a child cohort. Methods: We used paradata (i.e. information about the process of data collection) from the German IDEFICS cohort investigating dietary‐ and life style‐induced health effects on children to quantify recruitment effort and classify respondents as completing the recruitment early vs. late for baseline and follow‐up separately. Multilevel logistic regression models were used to investigate the association between recruitment effort and attrition at follow‐up (loss to follow‐up) adjusted for sociodemographic and health related variables. Results: Individuals who were late respondents at baseline and early respondents at the follow‐up had a higher chance of attrition (odds ratio 1.65, 95% confidence interval (CI) 1.19, 2.28) as compared to other groups. An investigation of reasons for non‐participation revealed that members of this group were more likely to be not reachable by phone. Conclusions: An extended recruitment effort at baseline of a child cohort study is not per se associated with a higher chance of attrition at follow‐up. Much care should be taken to collect valid telephone numbers.